The effect of digital drug and their damages - Salman Mahmood, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The phenomenon of digital drugs is one of the negative phenomena that resulted in the misuse of digital technology in particular and the misuse of technology in general, despite the long period of time it took to appear in western societies, but it is still unknown in developing societies. This is due to its nature and to the nature of the work of digital drugs, and it may be due to its strange name, which carries a mixture between it and natural or regular drugs, although they differ radically from the other. Digital drugs are actually audio clips and a mixture of sounds, beats, tones, or musical songs, or all together they send vibrations of different waves of different and varying degrees in power and intensity, with the aim of affecting the brain waves to simulate different moods or psychological states; cases of happiness may be power and creativity or ascension and flight. All of these designations are promoted by websites by people who promote digital drugs to attract and motivate teenagers and young adults to arouse their curiosity and exploration and addiction. Therefore, this dangerous phenomenon requires that it be an area to discuss the enactment of internal legislation and international treaties, because it leads to harm at the level of individuals and societies. In spite of the great efforts of the united nations organizations in finding international cooperation to com traditional drugs through its international conferences between 1902 and 1972, He urged each country to en act legislation in line with the provisions of international in statements In front of that legislative vacuum here is the danger that must be faced and filled with international agreements and domestic legislation to protect individuals.